A Novel Antiserum Against a Predicted Human Peripheral Choline Acetyltransferase (hpChAT) for Labeling Neuronal Structures in Human Colon - Jean-Pierre Bellier; Pu-Qing Yuan; Pu-Qing Yuan; Kenichi Mukaisho; Ikuo Tooyama; Yvette Taché; Yvette Taché; Hiroshi Kimura (Frontiers Media S.A., 2019)
Choline acetyltransferase (ChAT), the enzyme synthesizing acetylcholine (ACh), has an exon-skipping splice variant which is expressed preferentially in the peripheral nervous system (PNS) and thus termed peripheral ChAT (pChAT). A rabbit antiserum previously produced against rat pChAT (rpChAT) has been used for immunohistochemistry (IHC) to study peripheral cholinergic structures in various animals. The present study was undertaken to develop a specific antiserum against a predicted human pChAT (hpChAT) protein. A novel mouse antiserum has been successfully raised against a unique 14-amino acid sequence of hpChAT protein. Our Western blot using this antiserum (termed here anti-hpChAT serum) on human colon extracts revealed only a single band of 47 kDa, matching the deduced size of hpChAT protein. By IHC, the antiserum gave intense staining in many neuronal cells and fibers of human colon but not brain, and such a pattern of staining seemed identical with that reported in colon of various animals using anti-rpChAT serum. In the antibody-absorption test, hpChAT-immunoreactive staining in human colon was completely blocked by using the antiserum pre-absorbed with the antigen peptide. Double immunofluorescence in human colon moreover indicated that structures stained with anti-hpChAT were also stained with anti-rpChAT, and vice versa. hpChAT antiserum allowed the identification of cell types, as Dogiel type cells in intramural plexuses, and fiber innervation of colon muscles and mucosae. The present results demonstrate the specificity and reliability of the hpChAT antiserum as a novel tool for immunohistochemical studies in human colon, opening venues to map cholinergic innervation in other human PNS tissues.